2017
DOI: 10.3329/ajmbr.v2i4.31006
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of different green manures on the growth and yield of wheat

Abstract: Abstract:Green manures can enrich soils with organic matter and nitrogen. An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh, Bangladesh to evaluate the residual effects of different green manures on the growth and yield of wheat (BARI Gom-26). The experiment containing nine treatments were laid out in a randomized complete block design with three replications. The treatments were T 1 [No green manure + 100% Recommended dose of nitrogen (RDN)], T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…One of the major effects of these legumes was by significantly increasing soil pH (p < 0.05) compared to chemical fertilizers or non-treated plots (Table 3). This could be partly explained by pumping of leached cations to the root zones, and increased CEC in all green manure treated plots (Table 4), as also reported by others (Hoque et al, 2016;Couëdel et al, 2018). Interestingly, the effect was more pronounced in SRB treated plots, although application of root biomass alone had a significant effect on soil exchangeable cations.…”
Section: Contribution Of Green Manures To Physicochemical Soil Characteristicssupporting
confidence: 78%
See 3 more Smart Citations
“…One of the major effects of these legumes was by significantly increasing soil pH (p < 0.05) compared to chemical fertilizers or non-treated plots (Table 3). This could be partly explained by pumping of leached cations to the root zones, and increased CEC in all green manure treated plots (Table 4), as also reported by others (Hoque et al, 2016;Couëdel et al, 2018). Interestingly, the effect was more pronounced in SRB treated plots, although application of root biomass alone had a significant effect on soil exchangeable cations.…”
Section: Contribution Of Green Manures To Physicochemical Soil Characteristicssupporting
confidence: 78%
“…The study of N' Dayegamiye and Tran (2001) in Québec, Canada indicated that green manuring provided 15− 36 kg N ha -1 , and this contribution accounted for 25-31 % of the total N uptake of wheat. Hoque et al (2016) also noted that green manures exerted significant residual effects on grain and straw N concentration and total N uptake of wheat. Green manuring of poor soils also increased the quantity and quality of SOM, thereby improved the soil quality (N' Dayegamiye and Tran, 2001;Meena et al, 2018), soil water holding capacity and essential plant nutrients for the subsequent crops (Meena et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…BM/GM fb R+75% RDF yielded 15.49% more yield compared to 100% RDF (Table 3). The plots under this treatment had residual effects of Sesbania crop grown in the previous rice season and the finding was in accordance with (Hoque et al, 2017) who found yield advantage of 38% in wheat crop planted after the green manuring practices in rice field. The favorable soil environment due to the addition of OM and conservation of beneficial microbes due to the green and brown manuring practices in rice field might be responsible for the improved yield under BM/GM fb R+75% RDF (Hoque, Akter, & Islam, 2017).…”
Section: Grain and Straw Yield And Harvest Index (Hi)supporting
confidence: 88%